SYSTEM-DRIVEN (UN) FRAUD: TAFSIR APARATUR TERHADAP “SISI GELAP” PENGELOLAAN KEUANGAN DAERAH - Achdiar Redy Setiawan; Gugus Irianto; M Achsin (Universitas Brawijaya, 2013)
Abstract: System-Driven (Un)Fraud: Actor’s Meaning of the “Dark Side” of Local Government Financial Management. The purpose of this study is to uncover the actual practices of local government financial management in the smallest scope, namely SKPD (local government work units). This research focuses on the meaning of “the dark side”(a reality which stands behind the formal procedures and documentation that are displayed) from the actors who are government apparatus. Hermeneutics Gadamerian was chosen as the research methodology. Traces of